PENGARUH KENAIKAN TARIF DAN FASILITAS MELALUI ONLINE CUSTOMER REVIEWS TERHADAP MINAT KUNJUNGAN WISATAWAN LOKAL DI PANTAI KAWASAN BARON GUNUNGKIDUL - Diah Rumekti; Ardi Ariyanto (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study analyzes the effects of tariff increases and facility quality on local tourists' intentions to visit the Baron Beach Area in Gunungkidul, with online customer reviews (OCR) mediating the relationship between them. The research is backed by a sharp decline in domestic arrivals following significant retributive tariff hikes, infrastructure constraints, and rising digital complaints. A quantitative approach with a cross-sectional survey design was used to gather data from 400 respondents selected via quota sampling across 23 beach sites. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4. The results indicate that tariff increases and facility quality significantly influence visit intentions and OCR formulation. The mediation test shows that OCR serves as a strong partial mediator and is the dominant predictor of visit intentions. Destination managers are advised to improve tariff transparency and support facilities to optimize the destination's digital reputation